2017
DOI: 10.1016/j.actbio.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anticoagulants on the protein corona-induced reduced drug carrier adhesion efficiency in human blood flow

Abstract: Plasma proteins rapidly coat the surfaces of particulate drug carriers to form a protein corona upon their injection into the bloodstream. The high presence of immunoglobulins in the corona formed on poly(lactic-co-glycolic acid) (PLGA) vascular-targeted carrier (VTC) surfaces was recently shown to negatively impact their adhesion to activated endothelial cells (aECs) in vitro. Here, we characterized the influence of anticoagulants, or their absence, on the binding efficiency of VTCs of various materials via m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 58 publications
(95 reference statements)
0
24
0
Order By: Relevance
“…Flow through the chamber was initiated via a programmable syringe pump. Before the flow assays, particles were incubated in plasma in a similar manner as previously described in Sobczynski and Eniola‐Adefeso, with a few key differences. Prior studies with PLGA particles have shown that after ≥5 min of exposure to 100% (i.e., undiluted) plasma, the extent of the adhesion reduction was saturated with no additional reduction observed up to 60 min incubation time .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Flow through the chamber was initiated via a programmable syringe pump. Before the flow assays, particles were incubated in plasma in a similar manner as previously described in Sobczynski and Eniola‐Adefeso, with a few key differences. Prior studies with PLGA particles have shown that after ≥5 min of exposure to 100% (i.e., undiluted) plasma, the extent of the adhesion reduction was saturated with no additional reduction observed up to 60 min incubation time .…”
Section: Methodsmentioning
confidence: 99%
“…Since the depletion kits limited the amount of depleted plasma available, incubation of diluted plasma was employed, and particles were incubated for ∼1 hr (Supporting Information Figure S1). The 1 hr incubation time with 25% plasma was chosen here since similar levels of adhesion reduction were achieved with this condition, as compared to ≥5 min 100% plasma incubation, which represents the physiological scenario in vivo. Moreover, a recent study by Tenzer et al observed that a protein corona is established within 1 min of plasma exposure and that changes beyond this time, up to 4 hr, occurs only in the amount and not the types of bound proteins.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations